Grape berry vacuole: a complex and heterogeneous membrane system specialized in the accumulation of solutes - Fontes, N. (2011)
Vacuoles fulfill highly specialized functions depending on cell type and tissue and plant developmental stage. This complex and dynamic organelle is the main reservoir of grape berry cells, playing a major role during fruit development and ripening. Berry development is accompanied by modifications in size, composition, color, texture, flavor, and pathogen susceptibility, primarily because of changes in vacuolar content. Most aroma and flavor compounds are not evenly distributed in the berry, and the number and type of vacuoles may vary depending on the tissue (skin, flesh, and seeds). Together with the lytic and protein storage vacuoles widely distributed in plant cells, phenolic vacuoles are also implicated in cellular storage in grape cells. After veraison, when grape berry growth exclusively results from cell enlargement, tonoplast transporter proteins mediate a massive sugar import and water intake into the vacuole, leading to a large vacuolar expansion. The V-ATPase and V-PPase pumps create a proton electrochemical gradient across the tonoplast, which, in turn, energizes the uptake of charged and uncharged solutes. Several tonoplast proteins mediating the uptake of sugars, organic acids, water, ions, and anthocyanins have been cloned and some have been functionally characterized. The present review focuses on the storage function of vacuoles and on their structure and diversity in relation to development and ripening of the grape berry.